The dynamic structure of wages in Germany 1976 - 1984: A cohort analysis - Bernd Fitzenberger; Reinhard Hujer; Thomas E. MaCurdy; Reinhold Schnabel (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1995)
Based on social security data, this paper analyzes wage trends for full employed males by estimating (censored) quantile regressions as functions of age, cohort, education, and year. We test whether a parsimonious specification separating life cycle effects from macroeconomic effects can describe the dynamics of wages. Our results indicate that insider wages are uniformly affected by a acroeconomic trend. For some education groups, this also holds for entry wages. Since within-inequality stays fairly constant, the estimated profiles characterize the entire wage distribution. After controlling for age and cohort, also wage differentials across education remain roughly stable..
Keywords: 330; wage inequality; cohort analysis; decomposition of life cycle profile and time trend; quantile regressions; censoring; Lohn; Lebenseinkommen; Einkommensverteilung; Deutschland